Resistin: A Novel Diagnostic and Prognostic Biomarker for Metabolic Dysfunction-Associated Steatotic Liver Disease - Marwan N. Elgohary (The International Journal of Multiphysics, 2024)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) is a prevalent health problem affecting more than 1/3 of the world population. It has similar cardiovascular risk factors to those of the metabolic syndrome and represents an independent risk factor of atherosclerotic ischemic heart disease and chronic renal impairment with significant morbidity & mortality implications. Its long-term outcomes are liver fibrosis, cirrhosis, and hepatic carcinoma. More extensive research is still required to improve the diagnostic and therapeutic options for MASLD and its severe form, metabolic dysfunction-associated steatohepatitis (MASH. Resistin is an adipokine with pro-inflammatory properties, produced by adipose tissues & some inflammatory cells such as macrophages, monocytes as well as hepatic stellate cells. It contributes to the pathogenesis of MASLD inflammatory process & MASLD-induced fibrogenesis. Methods: This case-control study was performed in Zagazig University hospitals over a period extending from July 2023 till July 2024. It enrolled 69 Subjects, who were divided into 3 equal groups: MASLD, MASH & control subjects. The patients were evaluated by history taking, thorough clinical examination, abdominal ultrasonography, blood workup, and serum resistin level. Results: The study included 39.1% males and 60.9%females with a mean age of 43 years old. There was a statistically significant difference between the studied groups regarding body mass index (BMI), hemoglobin, platelet count, liver enzymes, total & LDL-cholesterol, triglycerides, blood glucose level & serum resistin level. The best cutoff values of serum resistin were ≥28.25 & ≥903.5 pg/ml in MASLD & MASH respectively. Conclusion: Serum Resistin level is a proper & valid serum biomarker for MASLD & MASH